Determination of the main flavonoids in ojo de gallo (Sanvitalia procumbens Lamarck) yerba extracts from three different sites as potential biomolecules - Baltazar-Vera, Juan Carlos; Valtierra-Olivares, Joel Everardo; Olalde-Portugal, Víctor; Ortíz-Canchola, Claudia; Rodríguez-Rodríguez, Carolina de Jesús; Abraham-Juárez, Ma. del Rosario (Revista de Ciencias Agrícolas, 2023)
This work focuses on determining the main flavonoids with medicinal effects present in the wild ojo de gallo plant endemic to the State of Guanajuato in Mexico. For this purpose, the concentration of kaempferol, catechin, and rutin was determined in the wild ojo de gallo grass collected from three different sites in the state of Guanajuato (Comedero Grande, Ex – Hacienda de Márquez, and Tejamanil). The dehydration process of the plant was carried out later to determine the concentration of the metabolites of interest using the high-performance liquid chromatography (HPLC) technique. A statistical analysis was carried out to determine the relationship between the concentration of each metabolite and the various collection sites, also considering the results of the fertility analysis. The results show that the highest concentration for kaempferol was obtained in Ex – Hacienda de Márquez with a value of 24.15 ppm, while for catechin and rutin, it was in Tejamanil reporting values of 26.52 ppm and 46.98 ppm, respectively. The statistical analysis shows no significant difference between Ex -Hacienda de Márquez and Tejamanil for the three metabolites. These results indicate that the site called Comedero Grande favors the presence of kaempferol and rutin while the site called Tejamanil favors the presence of catechin; this opens the possibility of future studies that allow finding the appropriate conditions to maximize the flavonoids of interest in this plant.